Implementation of the Pancasila student profile strengthening project (p5) in early childhood education (PAUD) - Ruswandi, Agus; Alviona, Andina; Hasna, Ghina; Amelia, Ine; Nabilla, Jihan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The purpose of this study was to measure the achievement of the project to strengthen the profile of Pancasila students (P5) at The Early Childhood Education unit. This study employs a quantitative research design using a survey method. The sampling technique used is simple random sampling with a margin of error of 5%. A total of 78 PAUD teachers in the Buah Batu District, Bandung City, West Java Province. The data collection method used in this study uses an online questionnaire distributed via Google Forms to each research participant consisting of 13 questions. Data analysis techniques using descriptive statistical analysis, namely by calculating the mean value of each indicator. The findings reveal that the reinforcement of P5 in PAUD settings has been achieved, as evidenced by 56.41% of teachers reporting adequate understanding of P5 and 47.43% indicating sufficient availability of P5-related documents. Statistical calculations show a final score of 66.3%, categorized as "Achieved".The results suggest that there are some areas that need to be improved, particularly in relation to teacher training, the availability of teaching modules and parental involvement in P5 implementation. Therefore, recommendations to improve the achievement of P5 implementation in early childhood education include improving teacher training and understanding, providing more resources and guidelines, and strengthening efforts to involve parents in children's character education process.